Analisis Aktivitas Pembelajaran Matematika ditinjau dari Kepercayaan Diri Siswa SMP Negeri 26 Makassar - Hamda, Hamda; Bernard, Bernard; Susil, Susil (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This research aims to describe students' mathematics learning activities in terms of self-confidence at UPT SPF SMPN 26 Makassar. This type of research uses descriptive qualitative methods. The subjects in this research were students in class VIII 2. Data collection techniques in this research were through questionnaires, observations and interviews. The research instrument consists of the researcher himself, questionnaire sheets, observation sheets, and interview guidelines. Data analysis techniques include data condensation, data presentation, and drawing conclusions. The results of the research show that (1) Students with low self-confidence have sufficient learning activities, this is because subjects with low self-confidence do not have a selfish nature by respecting friends' opinions; (2) Students with moderate self-confidence have good category learning activities, but sometimes feel lazy and embarrassed; (3) Students with high self-confidence have learning activities in the very good category, this is because subjects with high self-confidence are confident in their abilities, are responsible for their duties, dare to express opinions, have good development with an independent attitude and respect other people's opinions.